Repairable spare parts flow in a multi-echelon inventory system - Milićević, Milić R.; Sokolović, Vlada S.; Milenkov, Marjan A. (Vojnotehnički glasnik / Military Technical Courier, 2015)
This paper considers the problem of changing the value of selected characteristics for the operation of a two-level inventory system of maintainable parts depending on the flow of regenerated components in the inventory system. We analyzed the influence of the flow of regenerated components on the value of the coefficient of peripheral storage fill-rate, total costs and the average waiting time in the queue in peripheral warehouses, at different nominal values of the stocks in central and peripheral warehouses. The demand for spare parts in the peripheral warehouses is dependent on seasonal changes, modeled with an appopriate probability distribution.